PENGARUH LATIHAN TEMBAKAN DALAM KOTAK 16 TERHADAP AKURASI TEMBAKAN PADA SSB CHEVRON U-12 PEKANBARU - Wahyu Naidy; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is still lack of skill of fire in box 16 at athletes chevron U-12 Pekanbaru. Based on that problem the researcher to practice accuracy. This study aims to determine whether there is an offect of accuracy training on the skills of shooting in box 16 on athletes SSB Chevron U-12 Pekanbaru. So at the time of doing the skills of the shot to get maximum rusults. The form of this research is experimental (experimental, with population of SSB Chevron U-12 Pekanbaru),the data in this study is the entire population of 15. Intruments performed in this research is accuracy, which aims to measure how many athletes can do shoot in the box 16. After that, the data were processed with statistical, to test the normality by the lilifors test at a significant level of a (0.05) the hypothesis proposed is the effect of the accuracy training oh the firing skills in box 16. Based on statistical data analysis, pree-test of 0.1374 and post-test 0,0756, then the data is normal with an increase of 0.07. Based on t test analysis yielded T.hitung of 5.04 end T.tabel 1.761, rti T.hitung >T.tabel thus, there is an effect of accuracy training on firing skills in box 16 on SSB athletes Chevron U-12 Pekanbaru.Keywords : Accuracy, Shoot Skills In Box 16